2019
DOI: 10.1017/asr.2018.143
|View full text |Cite
|
Sign up to set email alerts
|

Mande hunters and the state: cooperation and contestation in post-conflict Côte d’Ivoire

Abstract: Abstract:This article analyzes the relationship between Mande hunters (dozos) and the Ivorian state in the prefecture of Ouangolodougou in northern Côte d’Ivoire. Having adopted a prominent security role during the violent conflict of 2002–2011, dozos have made continuing efforts to maintain their position in the post-conflict state. To negotiate their position, they draw on a performative repertoire, such as the display of powerful attributes in the context of processions. Although they have had to concede so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…200–203). In the security domain, although the state police and gendarmerie forces were redeployed across the north, many local dozo groups retained their informal policing roles in rebel-ruled territory, particularly concerning issues of cattle theft (Heitz-Tokpa, 2019, p. 156).…”
Section: Resultsmentioning
confidence: 99%
“…200–203). In the security domain, although the state police and gendarmerie forces were redeployed across the north, many local dozo groups retained their informal policing roles in rebel-ruled territory, particularly concerning issues of cattle theft (Heitz-Tokpa, 2019, p. 156).…”
Section: Resultsmentioning
confidence: 99%
“…Much has been written on the difference between 'illegality' and 'illicitness' (Roitman 2008), and often, scholars have identified local 'practical norms' that define the borders of licit behavior and govern the interaction between state authorities and traders (Titeca and Herdt 2010;de Sardan 2013;Heitz-Tokpa 2019;Tazebew and Kefale 2021). In Oshikango, there were indeed a certain number of practical norms that a researcher could have codified at any given moment.…”
Section: Notesmentioning
confidence: 99%
“…4.In the civil war in Sierra Leone, traditional hunters—the Kamajors—were involved as combatants (Muana 1997; Richards 1995, 2005). In the Ivorian civil war, dozos constituted a special company (Bassett 2004; Förster 2013; Hellweg 2004, 2011; Ouattara 2008; Hagberg & Ouattara 2010). …”
Section: Notesmentioning
confidence: 99%
“…In the perceived absence of the state—or at least due to the failure of the state to provide security and safety to its citizens—local defense groups have emerged. Research on self-defense groups and vigilante movements in West Africa (e.g., Förster 2013; Hagberg 2004a, 2006; Hagberg & Ouattara 2010; Hellweg 2004, 2011; Kirsch & Grätz 2010; Leach 2004; Muana 1997; Pratten 2006, 2008; Richards 1996) has shown that such movements tend to draw their legitimacy from local tradition and culture, in skillful combination with regional and national politics and the postcolonial state. This comparative study of self-defense movements in Burkina Faso highlights an important dimension of political rivalry and antagonism between the movements under study: the dozos and the koglweogos.…”
Section: Introductionmentioning
confidence: 99%